Immigration detention and the problem of time: lessons from solitary confinement. (2018) - Arbel, Efrat
In 2016, the Canadian Government launched an initiative to reform immigration detention, with the goal of creating a just and humane detention regime. In this paper, we argue that to achieve its stated goals, this initiative must address a core problem in the law of detention: the problem of time. This problem flows, in part, from there being no clear time limits on detention, and in part, from there being no clear standards for achieving release from detention. For insights into this problem, we turn to recent developments in the law of solitary confinement, which is similarly beset by the problem of time. Learning from solitary confinement, we argue that clear statutory time limits and meaningful independent oversight are necessary to ensure the just and humane regulation of detention. In their absence, the government's reforms may amount to window-dressing: detention will continue to be vulnerable to misapplication and misuse, and to destroy and dehumanise those in its care.